Ocorrência do Barley yellow dwarf virus e Cereal yellow dwarf virus, transmissibilidade do BYDV-PAV pelo pulgão Rhopalosiphum padi e reação de cultivares de trigo ao complexo vírus/vetor - Bianchin, Vânia (2008)
There are many diseases causing yield losses in wheat (Triticum aestivum L.) and, Barley yellow dwarf virus (BYDV) and Cereal yellow dwarf virus (CYDV) are the most important viral diseases of winter cereals. The first aim of this work was to identify the occurring species of BYDV and CYDV in some wheat growing regions of Brazil, collecting plants from Mato Grosso do Sul, Paraná, Santa Catarina and Rio Grande do Sul states, using monoclonal antibodies for DAS-ELISA diagnosis. It was observed the presence of BYDV-PAV, CYDV-RPV and plants with mixed infections of BYDV-PAV and CYDV-RPV in all sampled regions. A field experiment was conducted at the National Wheat Research Center (Embrapa Trigo) and 21 wheat cultivars were used to determine their susceptibility and tolerance. Evaluated traits were grain yield, yield components, number of tiller per plant, plant height, and weight of above ground plant parts and roots dry matter, virus titer and disease index obtained through disease incidence and severity of symptoms on plants. It was observed significant damage in all evaluated agronomic characteristics. Grain yield was the most affected characteristic with an average reduction of 47,94%. Fundacep 50, BRS Angico, BRS Guabiju and Embrapa 16 were highly susceptible and Ônix, BRS Timbaúva and Fundacep Nova Era less susceptible. None of the tested cultivars showed tolerance to the virus/vector complex. BYDV-PAV/vectors (Rhopalosiphum padi, Sitobion avenae e Schizaphis graminum). The BYDV-PAV transmission by the aphid Rhopalosiphum padi was also studied under controlled conditions. Temperature and the influence of time after inoculation on virus movement and replication were evaluated. Different parts of the plants were tested for virus titer purposes. Virus titer from the basal part of the leaves was lower than from the roots and higher than from the tip part of the leaves. Five days after virus inoculation, the virus had already been translocated to the root system. Time of inoculation was also compared and checked for virus detection purposes. Twelve hours after inoculation was less effective than 24, 36 and 48 hours. A single aphid was less efficient for transmitting the virus, and the highest virus titer was observed when plants were infested with five and ten aphids